Conversion From Sildenafil to Tadalafil: Results From the Sildenafil to Tadalafil in Pulmonary Arterial Hypertension (SITAR) Study. (November 2014) - Frantz, Robert P.; Durst, Louise; Burger, Charles D.; Oudiz, Ronald J.; Bourge, Robert C.; Franco, Veronica; Waxman, Aaron B.; McDevitt, Susanne; Walker, Susan
Purpose: Among phosphodiesterase type 5 inhibitors, tadalafil offers clinicians a once-daily alternative to 3 times daily sildenafil for the treatment of pulmonary arterial hypertension (PAH). This study assessed the safety and patient satisfaction with conversion from sildenafil to tadalafil. Methods: In this multicenter, prospective, 6-month study, patients with PAH were instructed to take their last dose of sildenafil in the evening and initiate tadalafil 40 mg/d the next morning. Patients completed the Treatment Satisfaction Questionnaire for Medication at baseline and 30, 90, and 180 days after transition to assess PAH symptoms and patient satisfaction. Safety was assessed on the basis of recorded adverse events (AEs). Results: Of the 35 patients who met the study criteria, 56% were receiving ≥2 PAH therapies. At the time of transition, the sildenafil dose ranged from 40 to 300 mg/d, with 20% of the patients on >20 mg of sildenafil 3 times daily. Transition to tadalafil was generally well tolerated, and the incidence of common AEs, except for myalgia, appeared to decrease over time on tadalafil therapy. Five (14%) patients switched back to sildenafil. A greater percentage of patients were satisfied than were dissatisfied after conversion to tadalafil (55% vs 19% at 90 days), while 26% felt about the same degree of satisfaction. Conversion to tadalafil resulted in significant improvement in patient ratings of therapy convenience. Conclusions: Transition of patients from sildenafil to tadalafil was usually well tolerated, with improved convenience and may enhance treatment satisfaction.